Outcome of Pterygium surgery with conjunctival autologous graft using suture and tissue glue at the tertiary eye center, Thimphu, Bhutan - Tashi Norbu; Zimba Letho; Dechen Wangmo; Deki Deki (Bhutan Health Journal, 2023)
ABSTRACT Introduction: Pterygium is a degenerative condition of the conjunctiva characterized by fibro vascular growth of tissue onto the cornea, often necessitating surgical treatment. Currently the conjunctival autograft technique using either suture or fibrin glue is the preferred method of treatment. The aim of the study was to evaluate the outcome of Pterygium surgery using sutures and glue to fix the graft.